Spinal Cord Glioneuronal Tumor with Rosetted Neuropil-Like Islands in Pediatric Age Group - Nil Comunoglu; Ozgur Kilickesmez; Buge Oz (Hindawi Limited, 2014)
Glioneuronal neoplasms are rare tumors. Recently, an unusual glioneuronal tumor histologically showing neuropil-like islands has been described. Here, we present such a tumor originating from spinal cord of a 14-year-old girl, who has scoliosis and urinary incontinence. Microscopically, the glial component was chiefly fibrillary astrocytic, punctuated by neuropil-like islands. Immunohistochemically, glial tissue was GFAP positive, and neuropil-like areas and big neurons were synaptophysin reactive. For astrocytic component Ki-67 proliferation index was 1% and p53 was immunonegative. This case is unique in that in the literature it is the second reported case in pediatric age group that is located at spinal cord.